Thermogravimetric analysis and kinetic study of raw and torrefied oil palm frond - Sang, Chang Siaw; Suriyati, Saleh; Noor Asma Fazli, Abdul Samad (AIP Publishing, 2023)
Torrefaction is one of the pre-treatment methods used to improve properties of biomass in order to be utilized as feedstock for pyrolysis and gasification processes. Prior knowledge of kinetic mechanism is significant before biomass can be utilized as feedstock for energy application. Thermogravimetric analysis (TGA) is an essential technique for kinetic study of raw and torrefied biomass. In this work, the effect of torrefaction on two different parts of oil palm frond (petiole and leaflets) on pyrolysis behaviour and kinetic parameter of the process were investigated. The results of this work showed removal of moisture and low molecular volatile matters contributes to the mass loss for both petiole and leaflet samples in stage Ⅰ. Coats-Redfern (CR) model is used in estimating activation energy (Ea) and pre-exponential factor (A) for stage Ⅱ (decomposition of hemicellulose and cellulose) and stage Ⅲ (decomposition of lignin). The regression with R2 values higher than 0.88 are obtained indicating the reliability of estimated kinetic parameters. The Ea and A values of petiole and leaflets show increment trends in both stage Ⅱ and stage Ⅲ. As comparison, torrefied petiole is the most suitable feedstock for pyrolysis process due to the highest HHV (23.55 MJ/kg) and produce highest char yield (41.21 wt.%).